Die Ukraine als Objekt russischer Großmachtansprüche : Sprachen, Identitäten und Diskurse - Goldt, Rainer (2023)
This volume brings together contributions on the background to the Russian attack on Ukraine from a (socio-)linguistic, linguistic and literary-historical and political perspective. The emphasis is not on day-to-day political events, but on facts and contexts that have received little attention to date. This reveals gaps in knowledge, misinterpretations and distortions that are deeply rooted not least in Western societies. Here, recognized experts bring together a wealth of background knowledge on the historical and current contexts of the Russian-Ukrainian conflict. In doing so, they help to reduce information deficits and correct misconceptions about the Eastern Slavic linguistic and cultural area.